Assessment of photoreceptor recovery and visual function utilizing adaptive optics and microperimetry in patients with surgically closed macular holes - Yuanyuan Liu; Xueli Yang; Wei Zhou; Jinguo Yu; Song Chen; Tiangeng He; Caiyun You; Xiangda Meng; Mengyu Liao; Yi Lei; Hua Yan (Photodiagnosis and Photodynamic Therapy)
Background: This study investigated the association between photoreceptor structural restoration and visual function outcomes in patients undergoing surgery for closed macular holes (MHs). Using adaptive optics scanning laser ophthalmoscopy (AOSLO) and microperimetry, we aimed to provide a more detailed understanding of photoreceptor recovery and visual improvement in closed MHs. Methods: We conducted a retrospective observational study of 31 eyes of 28 patients who underwent vitrectomy with internal limiting membrane (ILM) peeling to treat idiopathic MHs. Visual and structural outcomes were monitored 3 months to 2 years postoperatively: best-corrected visual acuity (BCVA), MH diameter and duration, optical coherence tomography (OCT) images, 4° retinal mean sensitivity (RMS), fixation rates, 68.2 % BCEA (binary contour ellipse area) of microperimetry, and cone density as measured by AOSLO. Based on the OCT findings, the patients were categorized into two groups: type 1 (closed MH with no neurosensory defect at the fovea) and type 2 (closed MH with a foveal neurosensory defect). Results: The analysis revealed that type 1 closures resulted in significantly better photoreceptor recovery, with cone cells migrating toward the fovea and forming dense islets, consistent with the integrity of the inner segment/outer segment layer on OCT. These patients also had better postoperative BCVA and higher RMS rather than fixation improvement, aligning with the improved cone density. In contrast, type 2 closures exhibited sparse cone distribution and a prevalence of large, high-density cells, possibly indicating glial cell proliferation and exposed retinal pigment epithelium (RPE). MH size, rather than duration or preoperative BCVA, was a key determinant of type 1 closure outcomes. Conclusion: AOSLO is a valuable tool for evaluating microstructural healing in MHs and reveals that type 1 closure, characterized by cone migration, leads to greater neuroretinal repair and improved BCVA and retinal sensitivity. Meanwhile, type 2 closures, marked by less photoreceptor recovery and higher glial proliferation, correspond to poorer visual function outcomes. This study highlights the role of photoreceptor density and migration in achieving optimal visual function post-surgery for MH closure.